Rare Presentations of Muscular Infiltrations in Classical Hodgkin’s lymphoma-A Case Series (Bangladesh Journal of Nuclear Medicine, 2023)
Hodgkin’s lymphoma (HL) is a malignant condition of the lymphoid system that involves supradiaphragmatic recesses, and typically presents with lymphadenopathy and spreads from one nodal group to the other. Skeletal muscle infiltration in HL is uncommon. Two cases of classical HL evaluated by an 18F-FDG PET-CT scan detecting multiple extranodal metastases along with skeletal muscle involvement are reported here, and their outcomes are discussed along with the importance of the PET-CT scan as a good imaging modality.Bangladesh J. Nuclear Med. 25(2): 143-146, 2022